2018
DOI: 10.1103/physrevd.98.086005
|View full text |Cite
|
Sign up to set email alerts
|

Rapid holographic phase transition with brane-localized curvature

Abstract: We study the finite-temperature properties of the Randall-Sundrum model in the presence of brane-localized curvature. At high temperature, as dictated by AdS/CFT, the theory is in a confined phase dual to the planar AdS black hole. When the radion is stabilized,á la Goldberger-Wise, a holographic first-order phase transition proceeds. The brane-localized curvature contributes to the radion kinetic energy, which allows us to substantially decrease the critical bubble energy. Contrary to previous results, the ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…The conclusions from the analysis of Sections 4.1 and 4.2 may in principle be generalizable to other theories beyond the SM, with the notable exception of models with an approximate conformal symmetry, which include scenarios with a pseudo-Nambu-Goldstone boson associated with a spontaneously-broken approximate conformal symmetry [54][55][56][57][58] (see also [35,36,[59][60][61]) (dilaton-like) as well as models which feature classical scale invariance [14,62]. Focusing on the former (though the following discussion does also apply to the latter scenarios), the effective potential then contains a scale-invariant term multiplied by a function that varies weakly with the scale [119]:…”
Section: The Case Of Conformal (Dilaton-like) Potentialsmentioning
confidence: 87%
“…The conclusions from the analysis of Sections 4.1 and 4.2 may in principle be generalizable to other theories beyond the SM, with the notable exception of models with an approximate conformal symmetry, which include scenarios with a pseudo-Nambu-Goldstone boson associated with a spontaneously-broken approximate conformal symmetry [54][55][56][57][58] (see also [35,36,[59][60][61]) (dilaton-like) as well as models which feature classical scale invariance [14,62]. Focusing on the former (though the following discussion does also apply to the latter scenarios), the effective potential then contains a scale-invariant term multiplied by a function that varies weakly with the scale [119]:…”
Section: The Case Of Conformal (Dilaton-like) Potentialsmentioning
confidence: 87%
“…It would then seem that plasma friction would play a negligible role on the expansion; however, for this to be the case, the amount of supercooling is typically required to be extremely large. To see this, we assume in the following that there is a relatively small number N of particles in the plasma that acquire a mass ∆m in the PT and produce transition radiation (notice that this is questionable in one of the prime examples -the holographic phase transition [28][29][30][31][32][33][34][35][36][37][38][39][40] -since there a large tower of particles will obtain a mass in the transition). The released energy is in this case of order ∆m 4 (or somewhat larger) and using (15) one finds that the Lorentz factor increases until it reaches the steady-state value…”
Section: The Wall Speedmentioning
confidence: 99%
“…The cross-terms in (35) then result in mixing between h and S. The mass eigenstate fields can be written as…”
Section: Singlet Extension Of the Smmentioning
confidence: 99%
“…Instead, for scenarios with large back-reaction, the universe inflates by (at most) a few e-folds and eventually completes the transition. In these cases the nucleation temperature is typically of the order of the EW scale, contrarily to what happens in most of the (small-back-reaction) frameworks considered in the literature [8][9][10][11][12]. Moreover, depending on the benchmark choice, the transition can end up with a reheating temperature smaller or larger than the nucleation temperature of the EW phase transition in the SM.…”
Section: Introductionmentioning
confidence: 98%
“…The holographic phase transition has been studied by a number of authors and it has been concluded to be of first-order [5][6][7][8][9][10][11][12][13]. However, in models with small backreaction on the gravitational metric, in order to avoid the graceful exit problem, one has to consider scenarios where the number of degrees of freedom in the CFT phase (i.e.…”
Section: Introductionmentioning
confidence: 99%